Single‐Shot Solid‐Phase Synthesis of Full‐Length H2 Relaxin Disulfide Surrogates. Issue 6 (9th January 2023) - Zhao, Rui; Shi, Pan; Cui, Ji‐bin; Shi, Chaowei; Wei, Xiao‐Xiong; Luo, Jie; Xia, Zhemin; Shi, Wei‐Wei; Zhou, Yingxin; Tang, Jiahui; Tian, Changlin; Meininghaus, Mark; et al.
Abstract: Chemical synthesis of insulin superfamily proteins (ISPs) has recently been widely studied to develop next‐generation drugs. Separate synthesis of multiple peptide fragments and tedious chain‐to‐chain folding are usually encountered in these studies, limiting accessibility to ISP derivatives. Here we report the finding that insulin superfamily proteins (e.g. H2 relaxin, insulin itself, and H3 relaxin) incorporating a pre‐made diaminodiacid bridge at A‐B chain terminal disulfide can be easily and rapidly synthesized by a single‐shot automated solid‐phase synthesis and expedient one‐step folding. Our new H2 relaxin analogues exhibit almost identical structures and activities when compared to their natural counterparts. This new synthetic strategy will expediate production of new ISP analogues for pharmaceutical studies. Abstract : The insulin family proteins (e.g. H2 relaxin, insulin itself, and H3 relaxin) incorporating a pre‐made diaminodiacid bridge (DADA) at A‐B chain terminal disulfide can be very easily and rapidly synthesized by a single‐shot automated solid‐phase synthesis. These new insulin analogues exhibit almost identical structures and activities when compared to their natural counterparts.